The Effects of Olopatadine Hydrochloride Treatment to the Tear Levels of IL-4 and IL-5 in Seasonal Allergic Conjunctivitis - Akyol, Nuray; Ulas, Fatih; Godekmerdan, Ahmet; Demir, Tamer (Turkish Ophthalmological Soc, 2005)
Purpose: The inflammatory response including TH-2 cells seems to be an additional mechanism to the type I hypersensitivity reaction in the pathogenesis of allergic conjunctival diseases. TH-2 cells produce the cytokines IL-4 and IL-5 which play important roles in production of IgE. The aim of this study is to determine the roles of these two cytokines in the pathogenesis of seasonal allergic conjunctivitis. It is also aimed to determine the effects of Olopatadine, an antiallergic agent which inhibits mast cell mediator release and HI receptor activity, on the tear levels of these two cytokines and the severity of the clinical symptom and the signs. Methods: Tear levels of IL-4 and IL-5 were measured by sandwich ELISA kit in thirteen healthy subjects and thirteen patients with seasonal allergic conjunctivitis; before and after 21 days treatment of olopatadine. Capillary tubes have been used to collect tears for the measurement of titers of IL-4 and IL-5. Treatment group was also evaluated for the signs and symptoms of the allergic conjunctivitis, side effects of the olopatadine. Results: Tear levels of IL-4 in patients with seasonal allergic conjunctivitis before and after the olopatadine treatment were significantly higher than those in controls (p< 0,001 and p< 0 ,01, respectively). In the treatment group, tear level of IL-4 after the treatment was significantly lower than before the treatment IL-4 level (p< 0,05). IL-5 level was under the detectable level in all samples. Clinical improvement of the signs and symptoms in the treatment group was significant, but scores did not reach to control level (p< 0,05 and p< 0,01, respectively). Side effect or intolerance to olopatadine were not observed. Conclusion: IL-4 plays a critical role in the pathogenesis of seasonal allergic conjunctivitis but IL-5 does not. IL-4, sign and symptom levels in the treatment group have not been decreased to the control levels, that is why we concluded olopatadine might not absolutely stabilize mast cells or some factors other than histamine might co-induce IL-4 secretion.
Keywords: Seasonal Allergic Conjunctivitis; IL-4; IL-5; Olopatadine